Distribuição normal assimétrica para dados de expressão gênica - Gomes, Priscila da Silva (2009)
Microarrays technologies are used to measure the expression levels of a large amount of genes or fragments of genes simultaneously in diferent situations. This technology is useful to determine genes that are responsible for genetic diseases. A common statistical methodology used to determine whether a gene g has evidences to diferent expression levels is the t-test which requires the assumption of normality for the data (Saraiva, 2006; Baldi & Long, 2001). However this assumption sometimes does not agree with the nature of the analyzed data. In this work we use the skew-normal distribution described formally by Azzalini (1985), which has the normal distribution as a particular case, in order to relax the assumption of normality. Considering a frequentist approach we made a simulation study to detect diferences between the gene expression levels in situations of control and treatment through the t-test. Another simulation was made to examine the power of the t-test when we assume an asymmetrical model for the data. Also we used the likelihood ratio test to verify the adequability of an asymmetrical model for the data.